Antifungal effect of plant extracts on Candida albicans biofilm on acrylic resin - Jonatas Rafael de Oliveira; Polyana das Graças Figueiredo Vilela; Felipe Eduardo de Oliveira; Kely Karina Belato; Cláudio Antonio Talge Carvalho; Antonio Olavo Cardoso Jorge; Luciane Dias de Oliveira (Brazilian Dental Science)
Objective: Evaluating the antifungal potential of Equisetum arvense L. (horsetail), Glycyrrhiza glabra L. (licorice), Punica granatum L. (pomegranate) and Stryphnodendron barbatimam Mart. (barbatimão) extracts, after Candida albicans biofilm formation on acrylic resin. Material and methods: C. albicans standard strain was cultured on Sabourauddextrose agar for 24 h at 37 °C. After standardized in a spectrophotometer, 100 ?L of the inoculum (106 cells/mL) and a sterile acrylic resin disc were maintained in Brain Heart Infusion broth supplemented with sucrose (5%), for 5 days at 37 ºC. The samples of the treated groups (n = 10) were separately exposed to a concentration of 50 mg/mL of each extract for 5 minutes or to nystatin (48.83 IU/mL). For the untreated group (control, n = 10), it was used sterile saline (0.9% NaCl). Biofilms were disaggregated from the acrylic resin discs by an ultrasonic homogenizer for 30 s. After decimal dilutions, sowings in Sabouraud-dextrose plates were made with incubation for 48 h at 37°C. Later, CFU/mL was verified and the values were converted to log10 and they had their statistical analysis done (ANOVA and Tukey Test, p ? 0.05). Results: It was found that all plant extracts and nystatin resulted in significant reduction of C. albicans biofilm (p < 0.01) compared to the control group (0.9% NaCl). However, all of them showed similar reductions to each other (p = 0.1567). Conclusion: There was biofilm formation of C. albicans on acrylic resin and all plant extracts were effective against this yeast, acting similarly to nystatin.